The Effect of Organizational Silence on Occupational Burnout - Kadhim Saaed, Hadeel; H. Raheemah, Salma; Hussein Shaalan, Uday (Opción, 2019)
The research aims at testing the relationship of influence and correlation be- tween organizational silence as the independent variable along with its reasons adopted in the study namely (the administrative and organizational reasons, the lack of experience, work-related concerns, as well as the fear of social iso- lation) and their influence on and correlation with the occupational burnout syndrome along with its three dimensions of (emotional exhaustion, blunting and personal accomplishment) As a dependent variable, and that through the implementation of the descriptive analytical approach. The study was carried out on (78) officers (i.e. government servants) from Second Rusafa’s Directo- rate General of Education, collectively representing the research community. A relevant questionnaire was used as a main tool to collect data and which was distributed across the studied sample of people and then recollected as being valid for the statistical analysis needed. The (spss) program was also used in the study along with the appropriate statistical methods including (the arithmetic mean, the standard deviation, correlation and regression, as well as Chronbach’s Alpha Coefficient and the Split-half method). The most prom- inent conclusions reached were seen in the existence of a silent organizational behavior of the individuals sampled in this study as well as a consensus on the opinion regarding the burnout syndrome, and the existence of a relation- ship of significance between the organizational silence and its dimensions with burnout syndrome except for the lack of experience/expertise dimension, as well as the existence of an effect relationship of the independent var- iable of organizational silence along with its dimensions (except for the lack of experience dimension) on the dependent variable of occupational burnout syndrome.